Sosialisasi Nilai-nilai Ukhuwwah Dalam Tafsir Al-Ahkam Karya Syekh Abdul Halim Hasan Binjai Di Desa Pekan Sawah Kecamatan Sei Bingai Kabupaten Langkat: Pengabdian - Syahrul Holid; Tanjung, Alfian; Aseandi, Riski; Hafifah, Mutia; Fatmawati, Rizky; Nisa Farza, T. Citra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service project aims to disseminate the values ​​of ukhuwwah (brotherhood) contained in Sheikh Abdul Halim Hasan Binjai's Tafsir Al-Ahkam to the women's religious study community in Pekan Sawah Village, Sei Bingai District, Langkat Regency. These values ​​include ukhuwwah Islamiyah, ukhuwwah Wathaniyah, and ukhuwwah Basyariyah, which are substantially contained in Islamic teachings and are important pillars in building a harmonious, inclusive, and religious society. The activity method uses a Community-Based Research and Service Learning approach, with implementation in the form of interactive seminars and participatory discussion sessions. The results of this activity are an increased public understanding of the values ​​of brotherhood and the creation of a conducive social climate and mutual respect for differences within the Muslim community. This activity also supports efforts to ground local interpretations in the socio-religious dynamics of society.